Strategi Kepala Sekolah dalam Membentuk Budaya Organisasi untuk Peningkatan Mutu Pendidikan di PAUD KB Bani Hamzah dan PAUD Darul Faqih: Principal’s Strategies in Building Organizational Culture to Improve Educational Quality at PAUD KB Bani Hamzah and PAUD Darul Faqih - Harmonika, Sri; Ariani, Silvia; Husmiati, Jumiatul; Wais, Abdul; Ahmad, Imam; Suhaeli; Layli, Ulpatul; Fu’adi, Zahratul (Lembaga Bale Literasi, 2025)
This study aims to analyze the role of organizational culture in improving the quality of education at PAUD KB Bani Hamzah and PAUD Darul Faqih, as well as to identify the strategies employed by school principals in shaping and internalizing a conducive organizational culture. Employing a qualitative approach with a case study design, data were collected through participatory observation, in-depth interviews with principals, teachers, and educational staff, and document analysis. Data were analyzed following Miles, Huberman, and Saldaña’s (2014) interactive model. The findings reveal that principals implemented participatory leadership, instilled shared values, habituated positive behaviors, strengthened collaboration, maintained open communication, and demonstrated exemplary integrity and work discipline. A strong and consistent organizational culture significantly enhanced teacher motivation, parental involvement, and the quality of learning processes and outcomes. In conclusion, the principals’ strategies in building and sustaining a positive organizational culture play a central and sustainable role in improving the quality of early childhood education.